2018
DOI: 10.1039/c8ra01317a
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput metabolomics enables metabolite biomarkers and metabolic mechanism discovery of fish in response to alkalinity stress

Abstract: High throughput mass spectrometry (MS)-based metabolomics is a popular platform for small molecule metabolites analyses that are widely used for detecting biomarkers in the research field of environmental assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…While the exact mechanism for this difference in metabolites across species is not known, there are a few possible mechanisms that could explain this trend. For example, the reduction in these metabolites may be linked to an increased energy demand in the livers of silver carp related to the processing of contaminants [ 94 , 95 , 99 ]. Alternatively, gill raker morphology of these two species differs, which enables silver carp to feed on smaller particles relative to bigheaded carp [ 100 , 101 ] arguably making silver carp a superior competitor [ 29 ], such that differences in liver metabolites may be driven by differences in food when these species are found sympatrically.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact mechanism for this difference in metabolites across species is not known, there are a few possible mechanisms that could explain this trend. For example, the reduction in these metabolites may be linked to an increased energy demand in the livers of silver carp related to the processing of contaminants [ 94 , 95 , 99 ]. Alternatively, gill raker morphology of these two species differs, which enables silver carp to feed on smaller particles relative to bigheaded carp [ 100 , 101 ] arguably making silver carp a superior competitor [ 29 ], such that differences in liver metabolites may be driven by differences in food when these species are found sympatrically.…”
Section: Discussionmentioning
confidence: 99%
“…There are six major families of proteins involved in salivary proteomics: proline-rich proteins (PRPs) including acidic PRP(aPRP), basic PRP (bPRP) and glycosylated PRP(gPRP), α-amylases, mucins, salivary (S-type) cystatins, histatins and statherin (Figure 1) (Castagnola et al, 2012a;Schulz et al, 2013a). Although some of their concentrations are 10-15 times lower than protein concentrations in plasma, the advancements in analytical highthroughput technology has greatly increased the detection sensitivity and specificity of proteomic biomarkers in saliva ( Sivadasan et al, 2015;Liang et al, 2016;Sun et al, 2018).…”
Section: Composition Of the Salivary Proteomicsmentioning
confidence: 99%
“…but some salivary proteins with specific roles are only produc ornejo et al, 2012). There are six major families of prot proteomics: proline-rich proteins (PRPs) including acidic P PRP) and glycosylated PRP(gPRP), α-amylases, mucins, s, histatins and statherin (Figure 1) (Castagnola et al, 2012 Although some of their concentrations are 10-15 times lo trations in plasma, the advancements in analytical high-throug atly increased the detection sensitivity and specificity of prote a ( Sivadasan et al, 2015;Liang et al, 2016;Sun et al, 2018).…”
Section: Composition Of the Salivary Proteomicsmentioning
confidence: 99%
“…In the past several years, high-throughput mass spectrometry (MS)-based metabolomics and sequencing techniques have been used to identify the responses of freshwater fish species exposed to different concentrations of saline-alkali stress. For Crucian carp ( Carassius carassius ), the metabolic changes in 7 key pathways, which include phenylalanine metabolism, glycine, serine and threonine metabolism, pyruvate metabolism, tyrosine metabolism, cysteine and methionine metabolism, aminoacyl-tRNA biosynthesis and butanoate metabolism, played a role in adaptation to extremely high alkalinity ( 14 ). For Nile tilapia ( Oreochromis niloticus ) in response to alkalinity stress, comparative transcriptome analysis revealed that the most significant pathway was energy metabolism ( 15 ).…”
Section: Introductionmentioning
confidence: 99%